Identifikasi Beban Kerja Melalui Penerapan Fisiologis Kerja Pada Pekerja Sentra Industri Sepatu - Asep Erik Nugraha; Rianita Puspa Sari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
Healthy, safe and comfortable working conditions need to be created to increase work productivity, ergonomic aspects of the work environment need to be considered so that workers perform their duties optimally. Worker complaints can indicate that there is an unbalanced physiological workload, it is necessary to measure workload at the industrial center. The shoe industry center is one of the largest centers but the production process is still conventional, all work activities are carried out in a sitting and bending position. The aim of this research to identify the workload of workers and measure and analyze the level of fatigue using the ergonomic approach method physiologically workers. The results showed the% CVL of workers in the range of 16.5% - 21.2% which indicates there is no fatigue in workers, while the Energy Consumption (KE) of workers has a value of 1.265 which shows the physiological workload classification is very light, with oxygen consumption (V02) in the range of values 0.7-0.8 which indicates work in the shoe industry center is a medium work classification.Key Words : Workloads, Ergonomics, Physiological Workload, Muscoletal Disrorder’s (MSD)